Green Synthesis and Antimicrobial Effects of Silver Nanoparticles Using Seeds of Plantago lanceolata - Al-Mudhafar, Suha M. A. (American Journal of Biology and Natural Sciences, 2026)
Nanotechnology has garnered the interest of researchers owing to the diminutive size and elevated surface-to-volume ratio of nanoparticles, resulting in alterations in chemical and physical properties. Green-synthesize silver nanoparticles (AgNPs) from the Plantago lanceolata plant and investigate their potential uses as antibacterial agents. Nanoparticles were constructed using P. c seeds extract by green synthesis method. The properties of nanoparticles were characterised using UV-vis, SEM, FTIR, and XRD then the antimicrobial activity and inhibition zone were measured using the diffusion method. The paper has managed to prepare silver nanoparticles (AgNPs) with the help of Plantago lanceolata seed extract, which has been proven by a color change to light yellow and a UK absorbance max at 432 nm. The SEM analysis showed the presence of nanoparticles of a spherical shape with 41.28 nm to 68.04 nm as the sizes, and XRD proved that they had a crystalline structure. Grameen AgNPs biosynthesized were also found to have high antibacterial activity against Gram-positive and Gram-negative bacteria. It is notable that the test with the greatest inhibition was obtained with Acinetobacter baumanii (22 mm) compared to the conventional antibiotic ampicillin which is considerably lower. These results show that AgNPs synthesized in green have a potential of being a powerful antimicrobial agent against multidrug-resistant microbes. The paper was able to show the green synthesis of silver nanoparticles (AgNPs) using Plantago lanceolata seed extract as a reducing agent which is both sustainable and environmentally friendly.